Individual differences in attributional style but not in interoceptive sensitivity, predict subjective estimates of action intention - Penton, Tegan; Thierry, Guillaume L.; Davis, Nick J. (Frontiers in Human Neuroscience, 2014)
The debate on the existence of free will is on-going. Seminal findings by Libet et al. demonstrate that subjective awareness of a voluntary urge to act (the W-judgement) occurs before action execution. Libet’s paradigm requires participants to perform voluntary actions while watching a clock hand rotate. On response trials, participants make a retrospective judgement related to awareness of their urge to act. This research investigates the relationship between individual differences in performance on the Libet task and self-awareness. We examined the relationship between W-judgement, Attributional Style (AS; a measure of perceived control) and interoceptive sensitivity (IS; awareness of stimuli originating from one’s body; e.g. heartbeats). Thirty participants completed the AS questionnaire (ASQ), a heartbeat estimation task (IS), and the Libet paradigm. The ASQ score significantly predicted performance on the Libet task, while IS did not - more negative ASQ scores indicated larger latency between W-judgement and action execution. A significant correlation was also observed between ASQ score and IS. This is the first research to report a relationship between W-judgement and AS and should inform the future use of electroencephalography to investigate the relationship between AS, W-judgement and RP onset. Our findings raise questions surrounding the importance of one’s perceived control in determining the point of conscious intention to act. Furthermore, we demonstrate possible negative implications associated with a longer period between conscious awareness and action execution.